Hemodynamic Signal Changes During Motor Imagery Task Performance Are Associated With the Degree of Motor Task Learning - Iso, Naoki; Moriuchi, Takefumi; Fujiwara, Kengo; Matsuo, Moemi; Mitsunaga, Wataru; Hasegawa, Takashi; Iso, Fumiko; Cho, Kilchoon; Suzuki, Makoto; Higashi, Toshio (Frontiers in Human Neuroscience, 2021)
Purpose: This study aimed to investigate whether oxygenated hemoglobin (oxy-Hb) generated during a motor imagery (MI) task is associated with the motor learning level of the task. Methods: This study included 16 right-handed healthy participants who were trained to perform a ball rotation (BR) task. Hemodynamic brain activity was measured using near-infrared spectroscopy to monitor changes in oxy-Hb concentration during the BR MI task. The experimental protocol used a block design, and measurements were performed three times before and after the initial training of the BR task as well as after the final training. The BR count during training was also measured. Results: The results showed that the number of BRs increased significantly with training (p<0.001). Visual analog scale scores also improved with training (p<0.001); furthermore, oxy-Hb concentration showed a main effect (p=0.001). However, the main effect of the region of interest (ROI) was not observed. The interaction was confirmed (p=0.029), and it was ascertained that the change in oxy-Hb concentrations due to training was different for each ROI. A significant correlation was observed between pre-motor area (PMA) and supplementary motor area (SMA) oxy-Hb concentrations and subjective MI vividness (p<0.04). Discussion: Hemodynamic brain activity during MI tasks may be related to task motor learning levels, as significant changes in oxy-Hb concentrations were observed after final training in the PMA and SMA of the brain. In particular, hemodynamic brain activity in the PMA and SMA was suggested to reflect the MI vividness of participants.